Why Decolonising Area Studies is Not Enough: A Case Study of the Complex Legacies of Colonial Knowledge-Making in the Indo-Myanmar Borderlands - Mandy Sadan (New Area Studies, 2020)
Decolonisation has become an important agenda both within academic institutions as well as within wider society in recent years. Yet the term is infrequently sufficiently critiqued or deconstructed to identify precisely what ‘the colonial’ refers to in specific academic contexts and therefore what the process of decolonisation should entail. It remains a relatively over-simplified agenda that easily becomes strategic rather than transformative of knowledge institutions. The focus on restructuring identifiable components, such as reading lists, limits discussion and critique of what decolonisation as an inherently more complex set of challenges should involve. The teaching and research related to Area Studies makes for an interesting example of the unresolved challenges of ‘decolonisation’ in academia. This paper reflects upon the complex discontinuities in understandings of ‘the Colonial’ in the Indo-Myanmar borderlands, challenging us to reflect more fully on what ‘decolonisation’ should entail in relation to academic interactions with this space. Specifically, it considers that region of the trans-Patkai mountain range where its corridors today connect modern north east India with the northern tip of Sagaing Division and Kachin State in Myanmar. The paper distinguishes itself from that broad literature on decolonisation by considering the ways in which colonial knowledge making intersects with contemporary knowledge making about this region, and the legacies of those historical constructions in the present. The often-unconscious ways in which academics and ‘experts’ are culpable in sustaining colonial representations that embed this region’s economic and political marginalisation, even when they assume that attention to a decentred ‘local’ voice is being magnified, means that there is also a need to think about the decolonisation of knowledge of this area more deeply. This article intends to contribute to that debate.